Pengaruh jumlah postingan instagram terhadap engagement rate pada bank syariah di indonesia - Ar-Rifa’i, Fahmi Amru (Maliki Interdisciplinary Journal, 2025)
The massive use of social media has expanded the ways in which Islamic banks in Indonesia communicate. This can make it easier for Islamic banks to build and maintain their image and relationships with customers. Through Instagram, Islamic banks can implement effective digital public relations strategies to achieve their goals. The purpose of this study is to find relevant results regarding the effect of the number of Instagram posts on the engagement rate of Islamic banks in Indonesia. The research method used is descriptive-quantitative. The data sources in this study were taken using the documentation method and an automatic Instagram engagement rate calculator on the SocialInsider website. The data analysis technique used is simple linear regression with the help of SPSS. The results of this study indicate that the number of Instagram posts has a significant negative effect on engagement rates. However, the total number of followers causes the engagement rate calculation to decrease, as it is assumed that many followers do not engage in digital public relations activities at Islamic banks in Indonesia. The author acknowledges that there are still many shortcomings in this study, including the lack of consideration of other factors that may affect engagement rates. Therefore, further research is needed to complement the results of this study.